Flagellar stators stimulate c-di-GMP production by Pseudomonas aeruginosa - Baker, A; Webster, S; Diepold, A; Kuchma, S; Bordeleau, E; Armitage, J; O'Toole, G (American Society for Microbiology, 2019)
Flagellar motility is critical for surface attachment and biofilm formation in many bacteria. A key regulator of flagellar motility in Pseudomonas aeruginosa and other microbes is cyclic diguanylate (c-di-GMP). High levels of this second messenger repress motility and stimulate biofilm formation. C-di-GMP levels regulate motility in P. aeruginosa in part by influencing the localization of its two flagellar stator sets, MotAB and MotCD. Here we show that while c-di-GMP can influence stator localization, stators can in turn impact c-di-GMP levels. We demonstrate that the swarming motility-driving stator MotC physically interacts with the transmembrane region of the diguanylate cyclase SadC. Furthermore, we demonstrate that this interaction is capable of stimulating SadC activity. We propose a model by which the MotCD stator set interacts with SadC to stimulate c-di-GMP production in conditions not permissive to motility. This regulation implies a positive feedback loop in which c-di-GMP signaling events cause MotCD stators to disengage from the motor; then disengaged stators stimulate c-di-GMP production to reinforce a biofilm mode of growth. Our studies help define the bidirectional interactions between c-di-GMP and the flagellar machinery.